2015
DOI: 10.1177/1933719115589410
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the MAPK/ERK Cell-Signaling Pathway in Uterine Smooth Muscle Cells of Women With Adenomyosis

Abstract: We investigated whether the myometrium might be intrinsically different in women with adenomyosis. We studied whether the mitogen-activated protein kinases/extracellular signal-regulated kinases (MAPKs/ERKs) and phosphoinositide 3-kinase/mammalian target of rapamycin/AKT (PI3K/mTOR/AKT) cell-signaling pathways, implicated in the pathogenesis of endometriosis, might also be activated in uterine smooth muscle cells (uSMCs) of women with adenomyosis and measured the production of reactive oxygen species (ROS), pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…25 The ERK/ MAPK signalling pathway was associated with the proliferation of uterine smooth muscle cells in the women with adenomyosis. 26 The overlapping of our findings with the previous studies may reflect the universal mechanisms underlying the adenomyosis and the reliability of our data.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…25 The ERK/ MAPK signalling pathway was associated with the proliferation of uterine smooth muscle cells in the women with adenomyosis. 26 The overlapping of our findings with the previous studies may reflect the universal mechanisms underlying the adenomyosis and the reliability of our data.…”
Section: Discussionsupporting
confidence: 79%
“…The IL‐6 signalling pathway was significantly increased in endometrial stromal cells after in vitro coculture with macrophage in adenomyosis which might play a role in the formation of ectopic tissues in adenomyosis . The ERK/MAPK signalling pathway was associated with the proliferation of uterine smooth muscle cells in the women with adenomyosis . The overlapping of our findings with the previous studies may reflect the universal mechanisms underlying the adenomyosis and the reliability of our data.…”
Section: Discussionsupporting
confidence: 79%
“…When lesions in the myometrium exhibit limited nodules, the condition is also referred to as adenomyoma. The etiology and molecular mechanisms of AM remain unclear (2). AM usually occurs in mothers >40 years old, with an incidence of 15-70% among this population sub-group (3).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the survival and apoptosis-related genes were upregulated or downregulated in the previous studies cited. Thus, the proliferation-and growth-related genes, including IGF1 (16)(17)(18)(19), IGF2 (19), vascular endothelial growth factor (VEGF) (40)(41)(42), hepatocyte growth factor (HGF) (43)(44)(45), nerve growth factor (NGF) (46)(47)(48), platelet-derived growth factor (PDGF) (16,49), epidermal growth factor receptor (EGFR) (16,17,49,50), fibroblast growth factor 2 (FGF2) (49,51,52) and mechanistic target of rapamycin kinase (mTOR) (53,54), were upregulated in both the ectopic and eutopic endometria from subjects with adenomyosis compared with the eutopic endometria from women without adenomyosis, while the anti-apoptotic or autophagy-related genes, such as BCL2 apoptosis regulator (BCL2) (38,(55)(56)(57), beclin 1 (BECN1) (58,59) and programmed cell death 4 (PDCD4) (60,61), were much higher in the ectopic and eutopic endometria than in the control endometria. Furthermore, the decreased expression of BCL2 associated X, apoptosis regulator (BAX) has been observed in adenomyosis, suggesting that the downregulation of apoptotic cell death machinery is a hallmark of adenomyosis (39).…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%
“…x) MTOR. Endometrial cells proliferate, migrate and survive by modulating the phosphatidylinositol 3-kinase (PI3K)/AKT/p-mTOR signaling pathway (53). The expression of p-mTOR has been shown to be higher in the ectopic endometrium than in the eutopic endometrium of patients with endometriosis or adenomyosis (53,54).…”
Section: Functional Pathways Of Adenomyosis Candidate Genesmentioning
confidence: 99%